Kikuchi's disease with secondary histiocytic lymphohistiocytosis - Pooja Pallavi; H.S. Rajani; D. Usha Rani; D. Narayanappa; N. Rashmi (Elsevier, 2024)
Background: Kikuchi-Fujimoto disease (KFD) presents with painful cervical lymphadenopathy, persistent high-grade fever, leukopenia, and deranged liver function tests. KFD usually has a benign course and is self-limiting but may sometimes cause fatal complications such as secondary histiocytic lymphohistiocytosis (HLH). Case report: We report a 13-year-old boy, a known case of thalassemia major on regular blood transfusions with post-splenectomy status and on chelators. He presented with persistent high-grade fever and cervical lymphadenopathy. The initial diagnosis of KFD was confirmed by lymph node biopsy. Given persistent fever, bicytopenia, and high ferritin levels, HLH was considered. Lymph node biopsy confirmed the diagnosis of KFD with secondary HLH. The child had neurological manifestations in the form of convulsions. He recovered with steroids and supportive care. Conclusions: This case report emphasizes that although KFD is benign, complications, including secondary HLH and neurological complications, may occur that need to be recognized and managed.